Effectiveness of using digital learning media (projectors) in mathematics learning - Afriska Della Imamiyah; Kharisma Putri Erlinawati; Mohammad Nurwahid (Nur Science Institute, 2025)
Despite the widespread promotion of digital technology integration in Indonesian schools, empirical evidence on how simple digital tools, such as projectors, are pedagogically used in mathematics classrooms remains limited, particularly from an in-depth qualitative perspective. Previous studies have primarily focused on learning outcomes, while paying less attention to classroom processes, teacher readiness, and contextual challenges. This study addresses this gap by exploring the effectiveness of using projectors in junior high school mathematics learning. Employing a qualitative case study approach, data were collected through classroom observations, semi-structured interviews, and document analysis at SMP Islam Bustanul Hikmah, involving 30 seventh-grade students and three mathematics teachers. The findings indicate that projector use supports students' conceptual understanding, enhances learning motivation, and promotes more interactive classroom engagement. However, technical constraints, variations in teachers' digital competence, and potential over-reliance on technology emerged as significant challenges. The study concludes that projectors can effectively support mathematics learning when integrated meaningfully into pedagogy and supported by adequate infrastructure, teacher competence, and school policy.